Posterior Pharyngeal Airway in Clockwise Rotation of Maxillomandibular Complex Using Surgery-first Orthognathic Approach - Choi, Jong Woo (Plast Reconstr Surg Glob Open, 2015)
BACKGROUND: Because obstructive sleep apnea is known to be an important preexisting factor causing chronic disease, many investigations have been done recently. There have been few reports regarding the posterior pharyngeal airway after clockwise rotation of maxillomandibular complex. Because the 2-jaw surgery in class III patients could cause obstructive sleep apnea or snoring, we investigated the posterior pharyngeal airway change of the clockwise maxillomandibular complex in the surgery-first orthognathic approach for the correction of class III dentofacial deformities. METHODS: A cephalometric evaluation of 35 patients with skeletal class III deformity was performed preoperatively and postoperatively. Three measurements of the posterior pharyngeal airway space (nasopharynx, oropharynx, and hypopharynx) and hyoid bone positions (the distance from palatal plane to hyoid bone and the distance from mandibular plane to the hyoid bone) were evaluated and correlated with the skeletal movement of the jaws using imaging software (V-Ceph, Osstem, Seoul, Korea). RESULTS: The preoperative airway space turned out to be enlarged in class III dentofacial deformities compared with those of normal persons. The preoperative P1, P2, and P3 in our cohort were increased and posterior nasal spine to hyoid bone and mandibular plane to hyoid bone were decreased compared with those of normal person’s data because the cohort consists of prognathic patients where the mandible is located in forward position. After 6 months, most values were nearly normal. CONCLUSION: Orthognathic surgery based on clockwise rotation of maxillomandibular complex did not cause severe posterior airway space changes at 6 months postoperation.